Fuel from waste as an attractive alternative to the energy industry in Poland - den Boer, Emilia (Instal, 2019)
One of the main problems of the waste management industry in Poland is the management of waste fuels, so-called RDF (Refused Derived Fuel), which can potentially be a source of electricity and heat, but the country currently lacks installations where it could, in accordance with the applicable standard, be recovered. In the light of the law, both in Poland and in the European Union, RDF is waste, which determines the requirements for its recovery. Currently, cement plants are the main recipient of waste fuels in Poland, but their processing capacity is limited. In addition, cement plants have high quality requirements for fuels, which can only be met by a small stream of RDF from municipal waste. The current lack of possibility to manage RDF causes both economic and ecological losses. The caloric fraction of waste separated in municipal waste treatment installations is stored, which creates a fire hazard, especially at high temperatures prevailing in the summer. In the context of rising coal prices and the need to increase the share of alternative energy sources in the national energy mix, RDF constitute very attractive and locally available fuel for the power industry. Fuels from municipal waste with lower calorific value (up to 11 MJ/kg) show a higher share of biodegradable fraction than high-energy fuels, which in the light of the applicable regulations, may be classified as RES. Their use allows to avoid a part of the fee for CO2 emission allowances, which in the context of the observed drastic increase in the prices of these allowances is undoubtedly a great advantage for a given power plant or heating plant.